Deskripsi Kejadian Malaria di Kecamatan Cempaka - Abdul Khair; Noraida Noraida (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2014)
Abstract: Based on the data obtained from Puskesmas Cempaka, it is known that malaria is an endemic disease in the Kecamatan Cempaka. The cases of malaria in the Kecamatan Cempaka in 2011, 2012, and 2013 respectively were 58, 60, and 61. Case Fatality Rate (CFR) of malaria in the Kecamatan Cempaka in 2013 was 3.18%. This study aimed to describe the distribution of malaria incidence by age, sex, place of residence, history of the scene, and the time of occurrence. This research is descriptive. The sample is the malaria patients who were living in the Kecamatan Cempaka, as many as 61 people. The results showed entire that the age of patients ranged from 8 to 63 years with an average of 29 years. The men are most affected by malaria (95%). Most malaria patients (49%) came from the Kelurahan Sei.Tiung. All the history of malaria incidence derived from outside the Kecamatan Cempaka, because most patients go home after work in the KabupatenTanah Bumbu (29%). Peak incidence of malaria is occurred in May of 2013 (27%). Epidemic of malaria has the potential to occur in the Kecamatan Cempaka due to the presence of Anopheles. Therefore, people need to avoid being bitten by Anopheles. The methods such as using the mosquito net while sleeping at night.Keywords: malaria incidence; Kecamatan Cempaka